Perception of smile esthetics among Indian dental professionals and laypersons - Santosh Kumar; Sumit Gandhi; Ashima Valiathan (Wolters Kluwer Medknow Publications, 2012)
Introduction : Patients' perceptions and expectations regarding their appearance play a significant role in treatment planning. The purpose of this study was to compare the perceptions of orthodontists, general dentists, and laypersons regarding smile esthetics after symmetrical and asymmetrical alterations in anterior teeth and their supporting tissues. Materials and Methods: Alterations were made in the crown length, crown width, midline diastema, and gingiva-to-lip relationship of the maxillary anterior teeth in the close-up photograph of a woman's smile. The attractiveness of the smile in the original image and in each of the modified images were assessed by orthodontists (n=40), dentists (n=40), and laypersons (n=40) and scored using a visual analog scale (VAS). The mean VAS scores were calculated for each photograph. ANOVA was used for comparisons between photographs and between groups. To determine threshold levels at which each group discriminated between esthetic and less esthetic dental features were determined by one-way ANOVA (F-test) followed by Newman-Keul's range test. Results : Orthodontists were found to be more critical when evaluating smile images compared to general dentists and laypersons. Symmetrical or asymmetrical alterations in the mesio-distal width of the lateral incisor of up to 2 mm was not perceived as unesthetic by general dentists and laypersons. Conclusion: Laypersons are more accepting of minor variations in anterior tooth size and alignment than orthodontists.